MOOD BOARD: THE PSYCHOLOGICAL WELLBEING ASSESSMENT FOR SPECIAL NEEDS STUDENTS IN CLASSROOM SETTING (Proceedings of International Conference on Special Education, 2023)
Achieving optimal psychological health has always been an important requirement to develop a holistic human being. With regards to the education ecosystem, especially with the negative impact on physical, psychological, and social challenges that were significantly influenced by the coronavirus (COVID-19) pandemic, the integral role that the teachers have to play in supporting the mental health and wellbeing of their students has grown exponentially. Despite the existence of multiple validated psychometric instruments, however, to accommodate the unique conditions of the participants, the aim of this study was to explore an interactive approach to assess the psychological wellbeing of special needs students in classroom setting. The development of the Mood Board was generated through reflecting on the psychological construct of the Malaysian Mood Scale, Malaysian Perceived Stress Scale and Malaysian Emotion Regulation Questionnaire. The construct of mood, perceived stress and emotion regulation were incorporated with (i) the traffic light analogy through the colours of red, yellow, and green; (ii) numbering – from one (1) to five (5); and (iii) emotions icons – smiling face with smiling eyes, anxious face, weary face. The participants will rate their current perceived emotional experience through the Mood Board, which can be completed physically and virtually, prior to the start of their respective classes. The opportunity to correspond the tangible data derived from the Mood Board with the real-life psychological, physical, and behavioural indicators expressed by the participants, teachers will have better understanding to observe the signs and reactions of the students and access support to manage their psychological distress. Participants also highlighted that they were more conscious of their mental processes. In general, the implementation of the Mood Board in a classroom setting provides a simple yet informative tool to assess, identify and monitor the psychological status of special need students.